Original articleBlood-brain barrier breakdown and cerebellar degeneration in the course of experimental neoplastic disease. Are circulating Cytokine-Induced Neutrophil Chemoattractant-1 (CINC-1) and -2α(CINC-2α) the involved mediators? - Michalak, Slawomir; Wender, Mieczysław; Michalowska-Wender, Grazyna; Kozubski, Wojciech (Folia Neuropathologica, 2010)
Cerebellar degeneration belongs to indirect effects of malignancy on the nervous system. Although the involvement of immune system is accepted as a hypothesis of its pathology, the clinical observations of ineffective immunomo-dulatory therapy suggest complex pathomechanisms, which await elucidation. The aim of this study was to prove the blood-brain barrier integrity, its relation to cerebellar degeneration and the role of circulating Cytokine-Induced Neutrophil Chemoattractant-1 (CINC-1) and Cytokine-Induced Neutrophil Chemoattractant-2α (CINC-α) in indirect effects of experimental malignancy. Two transplantable neoplasms: breast cancer (BC) and Morris hepatoma (MH) in rats were used in the study. The blood-brain barrier breakdown was clearly proved in the course of both malignancies. We observed also morphological signs of cerebellar degeneration in both models, with linear loss of Purkinje cells and homogenization changes more pronounced in breast cancer bearing rats. We have found a significant decrease of CINC-1 concentration in serum of rats with growing MH, however BC had no effect on CINC-1 concentration. Changes in serum CINC-2α concentrations in BC did not reach the level of significance, however in MH bearing rats the concentrations increased three weeks after tumour transplantation. In conclusion, we may state that the development of cerebellar degeneration as an indirect effect of experimental neoplasm can result from blood-brain barrier (BBB) breakdown and possible passage of neurotoxic factors. The decreased serum concentration of CINC-1 as neuroprotective agent and increased CINC-2α in late stage of MH may be considered for their contribution to cerebellar degeneration.